Managing Uncertainty through Values-Centric Leadership - Kimberly Miloch; Chris Ray; Abigail Tilton (Academic Chairpersons Conference Proceedings, 2022)
Crises force leaders to think in the short-term to address immediate needs. In navigating emergencies like COVID-19, it is vital that leaders remain values-focused, especially when considering short-term solutions that inevitably have long-term impact. This presentation examines values-centric leadership in the context of crisis communication, budget reductions, and strategic planning.
Keywords: Leadership; Values-centric Leadership; Crisis Communication; Budget; Strategic Planning